Biological, ecological and spatial analysis of a monument of park architecture - Hellenbach castle park in Marija Bistrica (Journal of Forestry, 2025)
Parks are an integral part of the area around castles and are mainly protected as castle grounds by the Act on the Protection and Preservation of Cultural Property (Official Gazette 69/99; 151/03; 157/03; 87/09; 88/10; 61/11; 25/12; 136/12; 157/13; 152/14; 98/15; 44/17; 90/18; 32/20; 62/20; 117/21; 114/22) and the Law on Nature Protection (OG 80/13; 15/18; 14/19; 127/19) The park within Hellenbach castle in Marija Bistrica was the subject of this research due to its extremely high historical and cultural importance at the national level. This paper is based on the analysis of the inventory of the dendrological species of Hellenbach park over the past forty years (inventories carried out in 1978, 2007, 2011 and 2021) and the changes that have occurred in terms of the presence of species and their shares over time. The last inventory, in the form of field work, measurement and data collection, was carried out by the authors of the paper in May 2021. All trees and bushes were measured, and the collected data was used to compare the current condition with the previous condition. The results of the analysis were used to define measures for the restoration and preservation of the park around the castle in the future. On this basis, the main guideline for landscaping the park, based on inventory, analysis and future use, is a combination of revitalization and conservation of the castle along with the park. Field measurements in this research determined that the health condition of the park is satisfactory, but that the restoration of the park's dendroflora is necessary. After the preparation of expert guidelines, the authors propose the expansion of the protected area of the park as a monument of park architecture on the entire area of 5.5 ha according to the Law on Nature Protection (OG 80/13; 15/18; 14/19; 127/19). The protection of the entire area of the historical park enables its full functional evaluation (its history, landscape, and usage), more active protection and maintenance. The management of castles and parks could be carried out through a management plan based on income from visitors, which would be an integral part of modern cultural tourism in Hrvatsko zagorje region.